Student usage patterns of Vle-Frog - Kamalludeen, Rosemaliza; Hassan, Azwani; Ahmad Nasaruddin, Nur Sakinah (Universiti Kebangsaan Malaysia, 2016)
Technology implementation of VLE-Frog as a learning management system (LMS) attempted to revolutionize the teaching and learning process of Malaysian school systems in accordance with 21st century demands. Despite the features and functions of VLE-Frog studied, there are very few studies done on VLE-Frog usage at secondary school level. Thus, there is a need to conduct a study on the factors that influence VLE-Frog usage among Malaysian secondary school students. The purpose of this study was to examine the factors that relate VLE-Frog usage among secondary school students. This study was conducted with the objectives to investigate VLE-Frog usage patterns among secondary school students in terms of their usage frequency and purposes as well as to explore students’ perceptions towards usage of VLE-Frog among the teachers. A case study approach was adopted by distributing questionnaires to 60 Form Four and Five students in SMK Taman Melawati. The results show that VLE-Frog features influenced students’ interest in using the platform and improved students’ IT skills. The findings of this study is hoped to inform students, teachers, and school administrators in improving current practices to increase awareness and usage of VLE-Frog in secondary schools.